Development of an application for identification and guidance on orthopedic foot diseases - Barros Botelho, Rafael; Bitu de Almeida, Marcelo; Romão da Rocha, Thais; Baumfeld, Daniel; Cavalcante Gomes de Souza Carvalho, Abrahão (Journal of the Foot & Ankle, 2025)
Objective: Develop software to identify the main orthopedic diseases affecting the feet and guide patients by assessing pain intensity and the application’s (APP) diagnostic accuracy. Methods: The software was developed by the Creation Department of Unichristus University. Over two months, 22 patients seeking orthopedics assistance for foot pain were recruited. During the scheduling, they were invited to participate in the study and received a link to download the APP. After signing the informed consent form and using the APP, the patient’s pain intensity and APP suggested results were collected and compared to the medical diagnosis recorded in electronic health records after consultation. Results: The APP was developed with information on the main orthopedic foot diseases. It showed high accuracy for hallux valgus (100%), plantar fasciitis (75%), metatarsalgia (66.67%), and calcaneal tendinopathy (66.70%). However, the overall concordance with medical diagnoses was 40.90%. Pain intensity primarily ranged between 6 and 8 (68.20%). Conclusion: The APP yielded positive results in identifying specific orthopedic foot diseases with relevant pain intensities but did not achieve high overall concordance. Further studies are needed to create more accurate diagnostic flowcharts. Level of Evidence; Diagnostic studies - investigating a diagnostic test.